2012
DOI: 10.1111/j.1475-097x.2012.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and perceptual responses to blood‐flow‐restricted resistance exercise with differing restrictive cuffs

Abstract: These findings suggest that low-intensity BFR resistance exercise does not appear to acutely negatively affect the vasculature. Also, cuff type will greatly affect cardiovascular and perceptual responses to BFR resistance exercise and thus is an important consideration in study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
137
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(160 citation statements)
references
References 27 publications
16
137
4
3
Order By: Relevance
“…In the present study, there was no evidence of a reduction in SV in the BFR bout. Most likely, this was due to the posture/positioning of participants such that the elevation of the legs provided some assistance to venous return that is not present with other modes of BFRE performed whilst seated or standing (Renzi et al 2010;Rossow et al 2012;Takano et al 2005). However, we have also shown previously that SV remains unchanged during unilateral bicep curl BFRE of small muscle groups (Brandner et al 2015), and while wider cuffs combined with lower restriction pressures are known to reduce the haemodynamic stress of BFRE (Rossow et al 2012), it remains untested as to whether a reduction in SV is a necessary consequence that is indicative of suitably prevailing BFRE conditions required to maximise the muscle adaptations observed with chronic BFRE training.…”
Section: Lp Trialmentioning
confidence: 98%
“…In the present study, there was no evidence of a reduction in SV in the BFR bout. Most likely, this was due to the posture/positioning of participants such that the elevation of the legs provided some assistance to venous return that is not present with other modes of BFRE performed whilst seated or standing (Renzi et al 2010;Rossow et al 2012;Takano et al 2005). However, we have also shown previously that SV remains unchanged during unilateral bicep curl BFRE of small muscle groups (Brandner et al 2015), and while wider cuffs combined with lower restriction pressures are known to reduce the haemodynamic stress of BFRE (Rossow et al 2012), it remains untested as to whether a reduction in SV is a necessary consequence that is indicative of suitably prevailing BFRE conditions required to maximise the muscle adaptations observed with chronic BFRE training.…”
Section: Lp Trialmentioning
confidence: 98%
“…Researchers have used a range of cuff widths for both the legs (4.5-18.5 cm) and arms (3-12 cm) [39]. Wider cuffs (13.5 cm) have been shown to cause greater ratings of pain and perceived exertion and to limit exercise volume during low-load BFR knee extension exercise when compared to narrow cuffs (5.0 cm) inflated to the same restrictive pressure [40]. Wider cuffs transmit pressure through soft tissue differently to narrow cuffs, which has obvious implications for subsequent training adaptations.…”
Section: Type Of Cuffmentioning
confidence: 99%
“…47 Several types of cuffs have been used such as elastic cuffs, nylon cuffs, and knee wraps. Larger cuff sizes produce significantly greater cardiovascular and perceptual responses compared to more narrow cuffs when a similar pressure is used 48 , and they produce arterial occlusion at lower pressures than narrow cuffs at rest 47 . However, when similar cuff sizes of different materials are used at the same target pressure, similar repetitions and exertion levels are found (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…50,51 It has been documented that different size cuffs can produce significant differences in cardiovascular responses so this should be considered when prescribing BFR exercise. 52 Despite this, in healthy adults very few side effects have been reported. 53 Also, studies have shown that it may not affect markers of coagulation [54][55][56] but may acutely increase fibrinolytic potential 54,56 .…”
Section: Safety Concernsmentioning
confidence: 99%